The position of the Arab press on the Islamic revolution in Iran 1979 (The position of the Syrian newspapers Al Thawra and Kuwaiti Al Raai Al Aam as a model) - Radi, Ass.Lecture Ghazi Eidan (Thi Qar Arts Journal, 2022)
The research studies the position of the Arab press on the events of the Islamic Revolution in Iran in 1979, and the two newspapers, the Syrian Revolution and the Kuwaiti public opinion, were chosen as a model for the study, which was divided into three sections. Economic, and reasons related to Shah Muhammad Reza Pahlavi’s management of the state. The second topic deals with the position of the Syrian newspapers, Al-Thawra and Kuwaiti Public Opinion, from the government of Shahpour Bakhtiar, and the Shah’s departure from Iran. The study relates to the position of the Syrian Al-Thawra newspapers and the Kuwaiti public opinion on the return of Mr. Ruhollah Khomeini, and the formation of the government of Mahdi Bazargan, as the Syrian newspaper Al-Thawra showed its bias towards Mr. Khomeini's leadership of the revolution, while the public opinion was satisfied with blessing the revolution's victory, considering it a popular revolution.